SP0147 ETHICAL ISSUES IN MEDICAL CANNABIS USE. (June 2019) - Alexander, Steve
Abstract : Background: The human history of Cannabis is chequered. We have evidence from the Ebers papyrus of ancient Egypt (1450 BCE) that 'shm-shm-t' was used as a medication for what appears to have been topical inflammatory issues. In the Atharva Veda (&x223C;1500 BCE), 'bhang' was considered one of the five sacred plants of India. The Old Testament refers to 'kaneh-bosm" as a component of a ceremonial anointing oil. In the UK"s Elizabethan era, Cannabis, as hemp, was grown widely for fibre to make rope and sail for the Royal Navy. In Victorian times, WB O"Shaughnessy brought back from India to the UK the medicinal use of Cannabis preparations for its reputed analgesic, anti-emetic, anti-inflammatory and anti-convulsant properties. In the modern era, Cannabis is a Schedule 1 drug in many countries - a legal status defined as having high abuse potential with no currently accepted medical value. Objectives: To consider the ethical issues associated with the use of Cannabis-derived preparations for medicinal purposes. Conclusion: Cannabis is unique among the Schedule 1 list, because extracts from the plant are licensed medicines in different parts of the world. The two most widely-researched metabolites from the plant are Δ 9 -tetrahydrocannabinol and cannabidiol (THC and CBD). The clinical uses of nabiximols (THC:CBD 1:1, combined with other minor cannabinoids) and nabilone (a synthetic THC analogue) for multiple sclerosis and antiemesis, respectively, as well as cannabidiol and dronabinol ((-)- trans -THC) for childhood intractable epilepsy and cachexia, respectively, identify that Cannabis -derived medicinal products have therapeutic value. Cannabis or THC in acute administration has a remarkably low association with mortality, however, there are a number of potential issues in the use of Cannabis itself rather than the above-mentioned extracts/compounds. Long-term heavy use of Cannabis is associated with the risk of addiction in about 10% of individuals. Severe anxiety attacks and psychotic episodes have been linked to higher doses of THC, although this has not been systematically identified. Both THC and CBD have identified metabolic profiles which might influence the turnover of other drugs. A major feature of the use of Cannabis itself is the variability observed. In part, this derives from the natural product nature of the plant and the associated variation in the metabolites between different parts of the plant, different plants, different methods of harvesting, storage as well as method, dose and frequency of administration, the subject"s prior exposure to Cannabis and the immediate environmental context. Even with the well-controlled clinical trials, there has been identified a variability in plasma levels of the administered agents. In those countries where medicinal Cannabis is more freely available, there are also concerns about patient use of black market sources. Disclosure of Interests: None declared